Potent urea and carbamate inhibitors of soluble epoxide hydrolases - Morisseau, Christophe (The National Academy of Sciences, 1999)
The soluble epoxide hydrolase (sEH) plays a significant role in the biosynthesis of inflammation mediators as well as xenobiotic transformations. Herein, we report the discovery of substituted ureas and carbamates as potent inhibitors of sEH. Some of these selective, competitive tight-binding inhibitors with nanomolar K(i) values interacted stoichiometrically with the homogenous recombinant murine and human sEHs. These inhibitors enhance cytotoxicity of trans-stilbene oxide, which is active as the epoxide, but reduce cytotoxicity of leukotoxin, which is activated by epoxide hydrolase to its toxic diol. They also reduce toxicity of leukotoxin in vivo in mice and prevent symptoms suggestive of acute respiratory distress syndrome. These potent inhibitors may be valuable tools for testing hypotheses of involvement of diol and epoxide lipids in chemical mediation in vitro or in vivo systems.